Implementation of the Principles of Sustainable Development in the Baikal Region: Historical, Cultural and Educational Aspects - I. G. Aktamov (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The issue of the implementation of certain aspects of the concept of sustainable development as a new civilizational paradigm in the conditions of the Baikal region is considered. The authors consider the experience of implementing the principles of sustainable development in the Baikal region, taking into account the socio-ecological, cultural and educational factors. The relevance of the study lies in the need to develop a new technology that can reduce the anthropogenic impact on the ecosystem of the lake itself and the coastal area. According to the authors, the most effective technology is the implementation of the principles of “education for sustainable development” (ESD). The solution to its problems is revealed through the educational efforts of teachers to preserve the ethnic culture of indigenous peoples, through the development of civic consciousness and patriotism of students, through the development of the intercultural competence of the individual. The novelty of the research is seen in the fact that the team of authors was one of the founders of education for sustainable development in the Republic of Buryatia, the creation of an international network of eco-oriented schools, the implementation of ESD courses at the university, practical environmental protection in the form of various grants and international collaboration for more than 25 years within the framework of a public organization. For the first time the historical periodization of the implementation of the principles of sustainable development in the Baikal region is presented in the article.